Interleukin 6 in pregnancy with gdm - Slagjana Simeonova Krstevska; Beti Zafirova Ivanovska; Viktorija Jovanovska; Igor Samardjiski; Aneta Sima; Saso Stojcevski; Igor Aluloski; Irena Todorovska; Vesna Livrinova; Vlatko Girevski; Daniel Milkovski (My University, 2019)
Abstract Background: Gestational diabetes melitus is a glucose intolerance diagnosed for the first time in pregnancy which may lead to maternal, fetal and neonatal unfavourable outcome. In GDM inflammatory markers like interleukin 6 are elevated and may provide informations on pathophysiology and prediction of perinatal risk. Aim: to evaluate the average concentration of interleukin 6 in GDM and normoglycemic women and the influence of body mass index on concentration of IL-6 in these women. Material and Methods: A case control study was made at the University Clinic for obstetrics and gynecology, Skopje in a period of one year. 100 pregnant women were selected from the pregnant women that performed 75g OGTT in the second trimester for sreening for GDM. Body mass index was calculated according to the terms of Institute of medicine and pregnant women were divided in 4 groups: GDM, BMI>25 (n=25); GDM, BMI<25(n=25); normoglycemic, BMI>25(n=25); normoglycemic BMI<25(n=25). Serum levels of IL-6 were analysed with ELISA method. Results: The medium values of IL-6 were higher in GDM compared to controls (2.77 ± 1.1 pg/ml vs 2.16 ± 0.5 pg/ml, p=0.0016). Pregnant women with GDM and BMI>25 vs GDM and BMI < 25 had statistically different values of IL-6 (2.58 ± 1.1 vs 2.19 ± 0.5 pg/ml, p=0.0019). Overweight women with GDM had significantly higher interleukin 6 than overweight women without GDM (3.06 ± 1.4 pg/ml vs 2.28 ± 0.7 pg/ml, p=0.021). Average value of IL-6 in GDM women with normal weight was 2.48 ± 0.8 pg/ml and significantly higher than normoglycemic women with normal weight, 2.04 ± 0.1 pg/ml, p=0.016. IL- 6 had insignificantly higher values in the overweight women from the control group compared to normal weight women from the control group (2.28 ± 0.7 pg/ml vs 2.04 ± 0.1 pg/ml; p=0.11). Conclusion: IL-6 is significantly higher in GDM compared to normoglycemic women. It can be used in addition with other biomarkers in eventual prediction of this condition.
Keywords: GDM; normoglycemic women; BMI; IL-6